PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE BERBANTUAN MEDIA GAMBAR TERHADAP KETERAMPILAN MENULIS KARANGAN ARGUMENTASI SISWA KELAS X SMA NEGERI 5 PADANG - Fitri, Yulia; R., Syahrul; Tamsin, Andria Catri (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2016)
ABSTRACT This article aims to look at the effects of describe the effect of the use of cooperative learning model Think Talk Write (TTW) aided image media against the argument essay writing skills class X SMA Negeri 5 Padang. This research data is the result of the test scores argument essay writing skills of students before and after using cooperative learning model TTW assisted image media. Instruments used in this research that tests the performance. The results showed that: First, the argument essay writing skills of students before using cooperative learning model TTW aided by media images that are in the qualification Fair (C) with an average value of 64.06. Second, the argument essay writing skills of students after using cooperative learning model TTW aided by media images that are in the qualification Good (B) with an average value of 81.08. Third, the use of cooperative learning model Think Talk Write TTW aided image media significantly influence the argument essay writing skills class X SMA Negeri 5 Padang. Kata kunci: pengaruh, model, pembelajaran, kooperratif, Think Talk Write,                        media, gambar, karangan argumentasi